Craig on the Resurrection: A Defense - Davis, Stephen T. (Socio-historical examination of religion and ministry, 2020)
This article is a rebuttal to Robert G. Cavin and Carlos A. Colombetti’s article, “Assessing the Resurrection Hypothesis: Problems with Craig’s Inference to the Best Explanation,” which argues that the Standard Model of current particle physics entails that non-physical things (like a supernatural God or a supernaturally resurrected body) can have no causal contact with the physical universe. As such, they argue that William Lane Craig’s resurrection hypothesis is not only incompatible with the notion of Jesus physically appearing to the disciples, but the resurrection hypothesis is significantly limited in both its explanatory scope and explanatory power. This article seeks to demonstrate why their use of the Standard Model does not logically entail a rejection of the physical resurrection of Jesus when considering the scope and limitations of science itself.